Denture stomatitis--presence of bacteria and yeasts - Jorge, A. E. [UNESP]; Broglio, L. Z.; de Almeida, O. P.; Jorge Júnior, J. (Arquivos Do Centro De Estudos Do Curso De Odontologia, 1990)
The presence of yeasts and bacteria was studied in 26 patients with denture stomatites, and the results compared with the data of the normal mucosa foi edentoulous patients, who used or not upper dentures. The use of dentures caused an increase in the amount of yeasts, and there was a correlation with the severity of the stomatitis. Gram positives cocci and bacilus predominated in all studied groups, but in cases of stomatitis there was an increase in the amount of Gram negative cocci and filamentous. These results suggest that besides yeasts, modifications of the bacteria flora can be relevant for the development of denture stomatitis.